PENINGKATAN KEPUASAN KERJA GURU MELALUI PEMBERIAN PENGHARGAAN DI SEKOLAH LUAR BIASA NEGERI DURI - Maidar Maidar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
Job satisfaction is an important target in human resource management because it will directly or indirectly affect work productivity. Conversely, high satisfaction is desired by leaders because it can be associated with the positive results they expect. High job satisfaction indicates that a school organization has been well managed with effective management. This School Action Research was located at SLB Negeri Duri, which was addressed to teachers at SLB Negeri Duri. The main reason was that based on the observation, teachers’ job satisfaction was still low. The population in this study was all 15 teachers at SLB Negeri Duri. Based on the results of the study, it was known that 1) The aspect of giving rewards brought by the tutor increased teachers’ job satisfaction in the second cycle. If the score the first cycle was 20, then the second cycle was better by getting a score of 32. In the aspect of teachers’ job satisfaction, it was found that the percentage in the first cycle was 53% with a good enough category and in the second cycle, it increased to 80% with a very good category. This situation showed that teachers’ job satisfaction increased through giving awards at SLB Negeri Duri.